2016
DOI: 10.1007/s40496-016-0112-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Sjögren’s Syndrome—from an Oral Perspective

Abstract: Oral symptoms are among the most distressing manifestations for patients with Sjögren’s syndrome (SS). The feeling of dry mouth is unpleasant, and hyposalivation may contribute to difficulty in speaking, chewing and swallowing and reduced quality of life. Reduced salivary flow increases the risk for dental caries and problems with prosthetic replacement. It seems that SS is not as frequently occurring as previously anticipated. Population-based prevalence studies on primary SS in Europe, conducted on large bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 90 publications
1
24
1
3
Order By: Relevance
“…B-cell hyperactivity represents a key hallmark of the pSS activity, reflecting in hypergammaglobulinemia, autoantibody production, and systemic manifestations of this disease. Serum beta-2-microglobulin is a biomarker of the lymphocyte hyperactivity [19]. This study revealed that the pSS patients presented higher values of serum beta-2-microglobulin than controls (2:84 ± 0:55 mg/l vs. 1:86 ± 0:44 mg/l, p < 0:0001).…”
Section: Disease Markersmentioning
confidence: 64%
See 1 more Smart Citation
“…B-cell hyperactivity represents a key hallmark of the pSS activity, reflecting in hypergammaglobulinemia, autoantibody production, and systemic manifestations of this disease. Serum beta-2-microglobulin is a biomarker of the lymphocyte hyperactivity [19]. This study revealed that the pSS patients presented higher values of serum beta-2-microglobulin than controls (2:84 ± 0:55 mg/l vs. 1:86 ± 0:44 mg/l, p < 0:0001).…”
Section: Disease Markersmentioning
confidence: 64%
“…Sjögren's syndrome, a complex autoimmune disease, is characterized by a broad spectrum of clinical and serological manifestations, dry eyes and dry mouth being the most common complaints [19].…”
Section: Discussionmentioning
confidence: 99%
“…Diverse external factors and natural alterations can lead reduced salivary flow 1,2 . This condition is known as hyposalivation 3,4 and affected individuals may or may not have a sensation of 'dry mouth', known as xerostomia 2,[5][6][7] . Both hyposalivation and xerostomia are conditions that can occur in an isolated manner, but xerostomia is most often the result of a reduction in salivary secretion and is therefore a strong indicator of hyposalivation [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…The causes of hyposalivation and xerostomia range from momentary factors, such as stress and anxiety [10][11][12] , to autoimmune diseases and chronic conditions, such as rheumatoid arthritis 13 , Parkinson's disease 13,14 , Sj€ ogren's syndrome 10,15,16 and diabetes mellitus [17][18][19][20][21] . The two conditions may also be found in patients requiring treatment for head and neck cancer 3,6,13,14,21 and those with diseases specific to the salivary glands 1,19 . Moreover, one of the major causes of reduced salivary flow is the use of particular medications 14,16,20,22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation